Empty sella in somatotropic pituitary adenomas; a series of 23 cases - Sharifi, Guive; Mohammadi, Esmaeil; Paraandavaji, Elham; Tavangar, Seyed Mohammad; Dabbagh Ohadi, Mohammad Amin; Jafari, Ali; Jahanbakhshi, Amin; Akbari Dilmaghani, Nader; Davoudi, Zahra; Smith, Timothy R.; Banihashemi, Gelareh; Azadi, Masoumeh; et al. (Frontiers in Surgery, 2024)
Purpose: Investigating empty sella syndrome in somatotrophic pituitary adenoma for possible etiology, complications, and treatment options. Method: Among over 2000 skull base masses that were managed in our center since 2013, we searched for growth hormone-producing adenomas. Clinical, surgical, and imaging data were retrospectively collected from hospital records to check for sella that lacked pituitary tissue on routine imaging. Result: In 220 somatotrophic adenomas, 23 patients had an empty sella with surgical and follow-up data. The mean age of sample was 46-years with a same male-to-female ratio. 5 cases had partial empty sella and the rest were complete empty sellas. The most common simultaneous hormonal disturbance was high prolactin levels. 6 had adenoma invasion into the clivus or sphenoid sinus and 10 had cavernous sinus intrusion. Peri-operative low-flow and high-flow cerebrospinal fluid (CSF) leaks were encountered in 1 and 2 patients, respectively, which were successfully sealed by abdominal fat. The majority of cases required growth hormone replacement therapy while it was controlled without any replacement therapy in 9 patients. No pituitary hormonal disturbance occurred after transsphenoidal surgery except for hypothyroidism in one patient. Conclusion: An empty sella filled with fluid can be detected frequently in pituitary adenomas especially in the setting of acromegaly. Pituitary gland may be pushed to the roof of sella and might be visible as a narrow rim on imaging or may be detected in unusual places out of sella. Pathophysiology behind such finding root from soft and hard tissue changes and CSF pressure alternations during abundant growth hormone production.